Спряжений теплообмін багатошарових полімерних плівок при струминному їх охолодженні - Горобець, В. Г. (Energy and Automation, 2017)
CONJUGATE HEAT TRANSFER OF COMPOZITE POLYMERIC FILMS WITH COOLING BY JETSV. GorobetsSingle-layer polymer films and composite materials have a wide scope in various sectors of the economy. In agriculture they can be used in the processing and storage of agricultural products, greenhouses and more. In the production of blown polymer films consisting of multiple polymers with different properties, developed the device in which to cool them during the transition from molten to the solid state is used bilateral air cooling airflow. Research has shown that regimeof streams flow in jets must be turbulent. There are engineering methods for calculating heat jet cooling systems are based on the criterion of dependencies, fair only to some cooling mode, which limits the applicability of the limited terms of experimental research. These dependencies not take into account such important factors as the uneven distribution of the local heat transfer coefficients on the surface, unisothermical character of film surface, the presence of vouchers areas near die and other factors. Using a calculation of coarse assumptions can lead to significant errors in determining the temperature conditions of the polymer film and does not allow with sufficient accuracy to design cooling systems, and identify ways to intensify the heat processes and increase performance cooling devices.The purpose of research - to develop mathematical models and numerical calculation of the transport processes in the jet air cooled tubular multilayer polymeric film and impact analysis of dynamical and geometrical factors on the conditions of the film formation.In the article the mathematical model of transport processes in the jet air cooled tubular multilayer polymeric film is developed. The numerical calculation and thermal performance obtained blown polymer films based on dynamic and geometric parameters of the cooling system. The analysis of the impact of the major factors in the performance of devices for production of multilayer blown polymer films is worked and recommendations to improve the performance of these devices are developed.